2010
DOI: 10.4028/www.scientific.net/kem.457.299
|View full text |Cite
|
Sign up to set email alerts
|

Computer Simulation of Lost Foam Process of Cast Iron

Abstract: Although several computer simulation codes have been developed to predict and prevent defects of lost foam castings, most of them are focused on aluminum alloy castings. This paper presents a new simulation method suitable for not only aluminum alloy but also cast iron. First of all, main assumptions and numerical schemes are as below: 1) Gas flow in the mold follows the D’Arcy’s law. 2) The gas pressure in the kinetic zone (gas gap) is uniform in each gas group and is solved by using the flow field of melt on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 12 publications
(16 reference statements)
0
2
0
Order By: Relevance
“…Shivkumar et al 6 investigated the thermal degradation of the foam pattern, gaseous products and a partially depolymerized viscous residue by using a similar method. Sun et al 7 & Ohnaka et al 8 directly observed the mold filling behaviors during lost foam casting by X-ray method. Numerical simulation is also a widely used method for the investigation of the filling process of lost foam casting.…”
Section: Introductionmentioning
confidence: 99%
“…Shivkumar et al 6 investigated the thermal degradation of the foam pattern, gaseous products and a partially depolymerized viscous residue by using a similar method. Sun et al 7 & Ohnaka et al 8 directly observed the mold filling behaviors during lost foam casting by X-ray method. Numerical simulation is also a widely used method for the investigation of the filling process of lost foam casting.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, considering characteristics of the lost foam casting, lots of researchers [2][3][4][5][6][7] pay more attention to understand characteristics of mold-filling and pyrolysis of cast iron. Through experiments and mathematical methods, they built the fluid melt and temperature distribution models of interface moving of metal and foam.…”
Section: Introductionmentioning
confidence: 99%